KECENDERUNGAN PENDEKATAN PEMBELAJARAN FIKIH DI STAIN BENGKULU - M, Sirajuddin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2012)
The purpose of this study was to determine the background of the birth of the tendency of approach to learning science of Islamic law (fikih) STAIN Bengkulu and also to explore the tendency of approach to learning sciences of Islamic law applied STAIN Bengkulu. This research is descrip-tive-qualitative, the analysis method used is the method of qualitative analysis and determination of population by purposive sampling technique. The research concludes that scientific approach to learning fikih trend developing in STAIN Bengkulu not be separated from thegrowing trends in Islamic scholarship and scholarly discourse of the early establishment of Islamic Higher Education (IHC). Therefore, with the development of contemporary science, the scientific approach to teaching fikih at STAIN patterned into two trends: First, the conventional learning approaches that only apply scientific knowledge and teaching jurisprudence that is textual, so this approach difficult to encourage students to think dynamically and contextually. Second, contextual learning approach that has developed a scientific discourse of fikih withthe development of contemporary science, such as how to build aharmonious household not only from the analysis of the fikih paradigm, but also analyzed and studied from the point of view of psychology.